A traces based system helping to assess knowledge level in e-learning system - Belgroun Brahim; Admane Lotfi (Journal of King Saud University: Computer and Information Sciences)
Given that knowledge level is one of most important aspects of e-learning platforms. Learners’ Interaction traces give very important information that describes their behavior when using e-learning platforms. Assessment of knowledge level can be completed by indicators related to interaction dimension (learner-learner or learner-system). Several methods have been developed in order to assess this attribute. Interaction traces analysis is one of most assessing tools used in e-learning applications. This paper deals with learning knowledge level assessment in e-learning platform. We propose a TBS (trace-based system) helping observers to assess this attribute.